RI-MACS: an innovative approach for future automation systems. (27th May 2009) - Checcozzo, Roberto; Rusina, Fulvio; Mangeruca, Leonardo; Ballarino, Andrea; Abadie, Claude; Brusaferri, Alessandro; Harrison, Robert; Monfared, Radmehr
The European funded Radically Innovative Mechatronics and Advanced Control Systems (RI-MACS) research project was initiated to address some of the challenges in the future automation systems. Its mission is to bring the innovation offered by the Information Technology (IT) domain into the production life cycle, improving some of the existing inflexibilities in typical manufacturing automation plants. In this paper, some of the key aspects of automation systems engineering that require changes to ensure future competitiveness are highlighted. An overview of current approaches to automation are reviewed in relation to wired and wireless networking, automation architectures, and design environments.